Wpływ wybranych czynników socjodemograficznych na aktywność ruchową pracowników biurowych = The impact of selected sociodemographic factors on motor activity of the office workers - Kozłowska, Ewelina; Kowalczyk, Anna; Rząca, Marcin; Kocka, Katarzyna (Journal of Education, Health and Sport, 2015)
Kozłowska Ewelina, Kowalczyk Anna, Rząca Marcin, Kocka Katarzyna. Wpływ wybranych czynników socjodemograficznych na aktywność ruchową pracowników biurowych = The impact of selected sociodemographic factors on motor activity of the office workers. Journal of Education, Health and Sport. 2015;5(6):141-156. ISSN 2391-8306. DOI 10.5281/zenodo.18418 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A141-156 https://pbn.nauka.gov.pl/works/564474 http://dx.doi.org/10.5281/zenodo.18418 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 05.06.2015. Wpływ wybranych czynników socjodemograficznych na aktywność ruchową pracowników biurowych The impact of selected sociodemographic factors on motor activity of the office workers Ewelina Kozłowska1, Anna Kowalczyk2, Marcin Rząca3, Katarzyna Kocka3 1Samodzielna Pracownia Epidemiologii, Uniwersytet Medyczny w Lublinie 2Studenckie Koło Naukowe przy Katedrze Onkologii i Środowiskowej Opieki Zdrowotnej Uniwersytetu Medycznego w Lublinie 3Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie STRESZCZENIE Wprowadzenie i cel pracy: Regularna aktywność fizyczna jest szczególnie ważna u ludzi narażonych na długotrwały bezruch wynikający m.in. z rodzaju wykonywanej pracy. Celem pracy było poznanie socjodemograficznych uwarunkowań aktywności ruchowej w grupie zawodowej pracowników biurowych. Materiał i metody: Przeprowadzono sondaż diagnostyczny wśród 937 pracowników zatrudnionych w biurach na terenie województwa lubelskiego. Zastosowano technikę ankietowania z wykorzystaniem autorskiego kwestionariusza ankiety. Zależność statystyczną pomiędzy aktywnością respondentów a wybranymi cechami socjodemograficznymi sprawdzono przy użyciu testu χ2 Pearsona. Wyniki: Wśród pracowników stwierdzono zróżnicowaną aktywność ruchową ze względu na płeć, wiek, stan cywilny, jak i miejsce zamieszkania. Czynna forma spędzania czasu wolnego dominuje wśród pracowników w wieku 35-45 lat (p=,0004) oraz osób po rozwodzie (p=,041). Mężczyźni (p=,014) oraz osoby w wieku 35-45 lat (p=,006) i mieszkańcy miast wojewódzkich (p=,021) częściej deklarują regularne podejmowanie minimum jednej formy aktywności fizycznej. Wnioski: Osoby poniżej 35 lat, jak i powyżej 45 lat, zamieszkujące tereny typowo rolnicze, samotne ze szczególnym uwzględnieniem grupy kobiet, wymagają podjęcia ukierunkowanych działań aktywizujących w środowisku pracy. Objęcie tych grup wsparciem informacyjnym może prowadzić do zwiększenia skuteczności realizowanych w miejscu pracy programów promocji zdrowego stylu życia. Jednym ze sposobów zwiększenia efektywności działań prozdrowotnych może być organizacja szczególnych form promowania aktywności z uwzględnieniem zróżnicowania preferencji ruchowych w obrębie poszczególnych grup socjodemograficznych. Słowa kluczowe: aktywność ruchowa, promocja zdrowia, pracownicy administracyjni. ABSTRACT Introduction an work aim: Regular physical activity is particularly important for people exposed to long-lasting immobility resulting among others from the type of work. An aim of work was to find out the sociodemographic determinants of physical activity in the professional group of office workers. Material and Methods: Diagnostic survey was conducted amongst 937 office workers employed in the Lublin Voivodeship. Survey technique was applied with a use of the author's questionnaire form. Statistical relation between the activity of respondents and chosen sociodemographic features was tested using the Chi2 Pearson test. Results: Amongst employees a diversified motor activity was stated due to sex, age, marital status as well as place of residence. Dynamic form of spending the leisure time dominates among employees at the age of 35-45 years old (p=,0004) and persons after divorce (p=,041). Men (p=,014) and those aged 35 to 45 years (p=,006), as well as residents of voivodeships (p=,021) more often declare a minimal one form of regular physical activity. Conclusions: Persons under 35 and above 45 years, residents of typically agricultural areas, lonely with particular reference to women's groups, require directed activation measures in the workplace. Providing these groups with an information support may lead to greater efficiency in promotion of a healthy lifestyle programs in the workplace. One possibility to increase the effectiveness of healthy activities can be an organization of special forms to promote the activity, including diversification of motor preferences within individual sociodemographic groups. Keywords: physical activity, health promotion, administrative personnel.